The influence of CRS and ICANS on the efficacy of anti-CD19 CAR-T treatment for B-cell acute lymphoblastic leukemia - Ma, Yuhan; Zhou, Hongyuan; Zhang, Jiaoli; Zhang, Qing; Li, Yujie; Xie, Ruiyang; Zhang, Bingpei; Shen, Ziyuan; Li, Ping; Liang, Aibin; Zhou, Keshu; Han, Lu; et al. (Frontiers in Immunology, 2024)
Background: Chimeric antigen receptor T cell (CAR-T) therapy has offered new opportunities for patients with relapsed/refractory B cell lymphoblastic leukemia (r/r B-ALL). However, cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) are the two most common toxicities following CAR-T cell therapy. At present, whether the occurrence of CRS and ICANS will impact CAR-T activity remains unknown; this affects the therapeutic efficacy of CAR-T. Methods: In this multicenter retrospective study, we enrolled 93 patients with r/r B-ALL receiving anti-CD19 CAR-T cell therapy at four medical centers. We evaluated their complete response (CR) rates, MRD-negative CR rates, and survival outcomes. Results: Among the included patients, 76 (81.7%) developed CRS and 16 (5.3%) developed ICANS. Fifteen patients experienced concurrent CRS and ICANS. However, no significant differences were noted in CR or MRD-negative CR rates between patients with and without CRS/ICANS. Furthermore, no significant difference was noted in leukemia-free survival (LFS) (p = 0.869 for CRS and p = 0.276 for ICANS) or overall survival (OS) (p = 0.677 for CRS and p = 0.326 for ICANS) between patients with and without CRS/ICANS. Similarly, patients with concurrent CRS and ICANS exhibited no differences in OS and LFS when compared with other patients. Multivariate analysis showed that the development of CRS and ICANS was not associated with any difference in OS and LFS. Conclusion: Patients with CRS/ICANS experience similar clinical outcomes compared with those without CRS/ICANS following anti-CD19 CAR-T therapy.